2020
DOI: 10.1093/nar/gkaa418
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent dynamics of synthetic and endogenous RSSs in V(D)J recombination

Abstract: Abstract Developing lymphocytes of jawed vertebrates cleave and combine distinct gene segments to assemble antigen–receptor genes. This process called V(D)J recombination that involves the RAG recombinase binding and cutting recombination signal sequences (RSSs) composed of conserved heptamer and nonamer sequences flanking less well-conserved 12- or 23-bp spacers. Little quantitative information is known about the contributions of individual RSS positions over th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(95 reference statements)
1
11
0
Order By: Relevance
“…2 B and C). Consistent with a previous biochemical study, G is least preferred at position 6 (23), and >80% of RSS heptamers containing G in this position are in the bottom fourth of RSSs reproducibly utilized in the SARP-seq method (Fig. 2B and Supplementary Dataset S1).…”
Section: The R/y Pattern In the Rss Heptamer Is Highly Predictive Of Rag1/2 Activitysupporting
confidence: 90%
“…2 B and C). Consistent with a previous biochemical study, G is least preferred at position 6 (23), and >80% of RSS heptamers containing G in this position are in the bottom fourth of RSSs reproducibly utilized in the SARP-seq method (Fig. 2B and Supplementary Dataset S1).…”
Section: The R/y Pattern In the Rss Heptamer Is Highly Predictive Of Rag1/2 Activitysupporting
confidence: 90%
“…Another shortcoming of the current implementation of the method is that it misses regulatory action at a distance. Indeed, our laboratory has invested a significant effort in exploring such long-distance regulatory action in the form of DNA looping in bacteria ( Johnson et al, 2012 ; Han et al, 2009 ) and V(D)J recombination in jawed vertebrates ( Lovely et al, 2015 ; Hirokawa et al, 2020 ). It is well known that transcriptional control through enhancers in eukaryotic regulation is central in contexts ranging from embryonic development to hematopoiesis ( Melnikov et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a research reported cryoelectron microscopy structures of synaptic RAG complexes at up to 3.4 Å resolution, which reveal a closed conformation with base flipping and base-specific recognition of RSSs ( Ru et al, 2015 ). Another study employed a single-molecule method to track the RAG–RSS interaction, which can provide a relatived complete kinetic description of the initial phases of V(D)J recombination ( Hirokawa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%